Pengaruh Pemberian Aroma Terapi Lemon Terhadap Pengurangan Nyeri Persalinan Kala I di Klinik Pratama Nurridha Desa Tanjung Selamat Kec. Sei Tuan Kab. Deli Serdang Tahun 2022 - Dina Kamariah; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Agustina Susilawati Tumangger (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Lemon aromatherapy is a type of aromatherapy that can be used to treat pain and anxiety. One of the substances contained in lemon is linalool which is useful for stabilizing the nervous system so that it can have a calming effect on anyone who inhales it. To explore the effects of using lemon aromatherapy in reducing pain in the first stage of labor at the Nurridha Pratama Clinic, Tanjung Selamat Village, Sei Tuan District, Deli Serdang Regency in 2022. The type of quantitative research with a research design using Quasy Experiment with a One Group Pre and Post Test Design. This research was conducted at the Nurridha Pratama Clinic, Tanjung Selamat Village, Sei Tuan District, Deli Serdang Regency in 2022. The population in this study was 15 people, then the sample was part of all the objects studied and was considered to represent the entire population (Notoatmodjo, 2015). The number of samples used was 15 people using the purposive sampling technique. The Data Analysis Technique used calculations with the Paired T Test. The data normality test uses the Shapiro-Wilk value, as a testing criterion, if the significant value is > 0.05 then it can be said that the collected data is normally distributed. The results of the statistical test obtained a significant value with P Value (0.000) <a (0.05) so that Ho is rejected. So it can be concluded that there is an effect of lemon aromatherapy on reducing labor pain in the first stage at the Nurridha Pratama Clinic, Tanjung Selamat Village, Sei Tuan District, Deli Serdang Regency in 2022.